2010
DOI: 10.1152/jn.00340.2010
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral State Dependency of Neural Activity and Sensory (Whisker) Responses in Superior Colliculus

Abstract: Rats use their vibrissa (whiskers) to explore and navigate the environment. These sensory signals are distributed within the brain stem by the trigeminal complex and are also relayed to the superior colliculus in the midbrain and to the thalamus (and subsequently barrel cortex) in the forebrain. In the intermediate layers of the superior colliculus, whisker-evoked responses are driven by direct inputs from the trigeminal complex (trigeminotectal) and feedback from the barrel cortex (corticotectal). But the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…This is a feature shared by other ascending sensory pathways, such as the trigeminothalamic pathway, and is known to be highly sensitive to behavioral state and neuromodulator influences (Castro-Alamancos 2002a, 2002b, 2004b. In fact, recent work has shown that whisker-sensitive cells in the superior colliculus are highly sensitive to changes in behavioral state (Cohen and Castro-Alamancos 2010a). Moreover, neuromodulators, such as acetylcholine, norepinephrine, and serotonin, are released in the superior colliculus during specific states and are likely to affect whisking and active touch signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a feature shared by other ascending sensory pathways, such as the trigeminothalamic pathway, and is known to be highly sensitive to behavioral state and neuromodulator influences (Castro-Alamancos 2002a, 2002b, 2004b. In fact, recent work has shown that whisker-sensitive cells in the superior colliculus are highly sensitive to changes in behavioral state (Cohen and Castro-Alamancos 2010a). Moreover, neuromodulators, such as acetylcholine, norepinephrine, and serotonin, are released in the superior colliculus during specific states and are likely to affect whisking and active touch signals.…”
Section: Discussionmentioning
confidence: 99%
“…In the superior colliculus, we measured spike probability during a long time window (2-80 ms poststimulus) or several short time windows. Peak1 (2-10 ms), peak2 (11-20 ms), and peak3 (21-80 ms) time window responses were calculated because they reflect responses of different origins and with different sensitivities to behavior (Cohen and Castro-Alamancos 2010a, 2010b, 2010cCohen et al 2008). All data are expressed as means Ϯ SE unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we propose further that RBD entails disinhibition of neural circuits that contribute to the production of defensive and aggressive behaviors, including but not limited to the superior colliculus. In support of this proposal, cholinergic neurons in the laterodorsal tegmental nucleus and the pedunculopontine tegmental nucleus, which are vulnerable to degeneration in the α-synucleinopathies [81,82], project to the superior colliculus [83,84] and may modulate its activity [85]. …”
Section: A Multicausal Multilevel Approach To Rbdmentioning
confidence: 99%
“…Therefore, in higher species it possibly acquired new roles including multisensory integration (Alvarado et al, 2009) for example and visual information processing is most important function of this area. The visual system, particularly the retinotopic SC-circuit (Chan et al, 2011), is intensely activated during REMS (Cohen & Castro-Alamancos, 2010), and all dreams essentially have visual experiences (Nir & Tononi, 2010). Sprenger et al (2010) recently studied kinematic parameters of REMs during REMS and suggested that REMs may be related to exploratory saccadic behavior during awake to remember visual stimuli.…”
Section: Superior Colliculus May Play An Essential Role In Integratinmentioning
confidence: 99%